The influences of alkaloids of Chelidonium majus L., Colchicum autumnale L, Catharanthus roseus (L.) G.Don and Vinca minor L. on malignant neoplasms, the review of modern researches. - Pavlenko , Oleksii; Strokina , Iryna (The Ukrainian Scientific Medical Youth Journal, 2023)
natural alkaloids of Chelidonium majus L., Colchicum autumnale L. and Catharanthus roseus (L.) G.Don are anticancer agents. Some of them, such as colchicine, vincristine and vinblastine, are used in modern medicine, as chemotherapy medicines against malignant neoplasms, some of them are effective supplement to conventional methods or works to prevent cancer onset (chelidonine, sanguinarine, chelerythrine, protopine and allocryptopine). The effect of mitotic poisons that are alkaloids of Colchicum autumnale colchicine, Catharanthus roseus vincristine and vinblastine against malignant neoplasms began to be studied in the last century, the fact of mitotic spindle violation is given in a large number of works. However, the mechanisms of apoptosis under their influence have been little studied. The alkaloids of Chelidonium majus and Vinca minor L. have been much less studied, both in clinical studies and experimental ones, including insufficiently researched their anti-proliferative action, the ability to cause apoptosis and its possible mechanism. The research of apoptosis mechanisms caused by natural antitumor agents, will allow creating more effective and saving medicines based on the active ingredients of plant raw materials in the future. The aim of the paper was the analysis of the effect of the main alkaloids of Chelidonium majus, Colchicum autumnale, Catharanthus roseus and Vinca minor on malignant neoplasms and the mechanisms of such an influence with the help of analytic review of foreign and Ukrainian literature for the period 2002-2023 using medical database PubMed. The researched data obtained on cell lines, laboratory animals (in vitro) and clinic studies were analyzed. According to the analysis of the literature of recent years, the cytotoxic and anti-proliferative effects of natural alkaloids of Chelidonium majus chelidonine, Colchicum autumnale colchicine, Catharanthus roseus vincristine and vinblastine and Vinca minor vincamine on malignant neoplasms can be considered proven. Colchicine caused apoptosis in high doses, chelidonine, on the contrary, caused apoptosis of malignant cells in relatively low doses; in large doses it caused autophagy. The signaling pathways of apoptosis mechanisms of malignant cells under the influence of chelidonine, colchicine, vincristine, vinblastine and vincamine are much less studied and require additional research. Most of the results support the mitochondrial pathway, but there is a view in favor of the receptor-mediated pathway. The medicine, which contained alkaloids of Chelidonium majus, showed a positive effect when used in combination with conventional antitumor therapy. Chelidonium majus and Vinca minor alkaloids are candidates for their use